Keterampilan Guru Dalam Menerapkan Variasi Media Pembelajaran Di Kelas II SDIP YLPI Pekanbaru - Rizka, Dhea; Febrina Dafit (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to find out how the teacher's skills are in applying media variations at SDIP YLPI Pekanbaru. This study uses qualitative research with descriptive methods. This study used three data collection techniques, namely interviews, observation and documentation. The data analysis technique used is according to Miles and Huberman. The results of the study show that teachers already have good skills in applying media variations. The media used have varied, namely power points, learning videos, pictures and others. The application of the media used has adjusted to the characteristics of the students and the design of the lesson plan used. The skills possessed by the teacher are in the form of relevance, teacher ability, ease of use, availability and usefulness.